Identification of new antibacterial targets in RNA polymerase of Mycobacterium tuberculosis by detecting positive selection sites. (April 2018) - Wang, QingBiao; Xu, Yiqin; Gu, Zhuoya; Liu, Nian; Jin, Ke; Li, Yao; Crabbe, M. James C.; Zhong, Yang
Graphical abstract: Highlights: Collect and identify 4 subunits and 13 sigma factors of RNA polymerase in 13 strains of Mycobacterium genus. Construct phylogenetic trees of 17 important genes of Mycobacterium genus, and detect relevant positive selection sites. We found the regions near 933Cys and 935His on rpoB subunit might be a new attractive target for anti-tuberculosis drugs. Abstract: Bacterial RNA polymerase (RNAP) is an effective target for antibacterial treatment. In order to search new potential targets in RNAP of Mycobacterium, we detected adaptive selections of RNAP related genes in 13 strains of Mycobacterium by phylogenetic analysis. We first collected sequences of 17 genes including rpoA, rpoB, rpoC, rpoZ, and sigma factor A-M. Then maximum likelihood trees were constructed, followed by positive selection detection. We found that sigG shows positive selection along the clade ( M. tuberculosis, M. bovis ), suggesting its important evolutionary role and its potential to be a new antibacterial target. Moreover, the regions near 933Cys and 935His on the rpoB subunit of M. tuberculosis showed significant positive selection, which could also be a new attractive target for anti-tuberculosis drugs.